Possibilidades do Google Workspace for Education no ensino de arte - Cadore, Rejana Cera (2022)
The present study, linked to the Professional Master's Course in Network Educational Technologies (PPGTER), in the Research Line Development of Educational Technologies in Network at UFSM - RS, has as its main theme the use of Google Workspace For Education resources for the art teaching. It was sought to analyze the extent to which technological tools can assist in learning and enhance educational planning in the area. The Product is a didactic sequence, consisting of four workshops, in which different Google resources were used. The scope of the research is the discipline of Art for students of the 6th year of a Santa Maria city elementary school - RS. For the development, the action-research methodology was adopted, starting with a theoretical bibliographic analysis and, later, divided into four stages: the first stage of the research consists of the planning and organization of the workshops; the second to implement the didactic sequence at school; the third contains the discussion and analysis of the data and the fourth is dedicated to the production of digital educational material in order to help educators in the use of Google Workspace for Education resources in the planning of face-to-face, hybrid and virtual classes. The production of data will take place through an initial quiz and another at the end; observations (recorded based on pre-established criteria) and visual productions by students. The analysis of the information produced made it possible to verify how the resources help the pedagogical proposals, pointing out the facilities and difficulties of their use. The culmination is the elaboration of the final product of this work, which will consist of a didactic sequence, to be shared with the educational network and for other educators who may be interested in the potential of Google Workspace for Education and use them in their teaching practices.